Degree of pollution by benthic litter in beaches in Salvador, Bahia, Brazil - Fernandino, Gerson; Elliff, Carla Isobel; Silva, Iracema Reimão (Scientia Plena, 2015)
Benthic litter has become a problem not only to the environment, but also to managers, due to its difficult access. Thus, little is still known about its impacts and behaviors as a type of pollution. The objective of the present study was to carry out a quali-quantitative analysis of the benthic litter of three beaches in Salvador, Brazil, so to investigate the sources of the pollution and possible mitigating actions. Three sampling campaigns were carried out between the years of 2012 and 2013. Transects measuring 100 m were placed perpendicularly to the coastline at each beach and, using scuba diving equipment, all benthic litter was gathered up to 1 m to each side of the axis cable. All items were sorted and analyzed regarding the type of material and possible sources. An adapted CCI was used to classify each beach and variance was analyzed through the Kruskal-Wallis test among sites and dates. During this period the beaches varied from very clean to extremely dirty regarding the accumulation of benthic litter. Plastic was the most common type of material and factors such as proximity with possible sources of pollution and hydrodynamics played an important role in the observed results. There were no significant differences among sites and dates. Actions to promote public awareness among the population that frequents these beaches are crucial to mitigate the situation, considering that the main litter sources were local. Moreover, current public beach cleaning efforts have shown to be ineffective.